Abstract of the returns of votes on proposed amendments to the Constitution : submitted to the people of Massachusetts for their ratification or rejection, May 23, 1855 (William White, printer to the State, 1856)
1856 Abstract of the returns of votes on the proposed amendments to the state constitution, submitted to the people of Massachusetts for their acceptance or rejection on May 23, 1855. Included were the votes by county and the aggregate result.